Supply Chain Model for Universities Management According to Education Criteria for Performance Excellence in Thailand - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The research was aimed to study and to evaluate the appropriateness of supply chain model for universities management according to education Criteria for performance excellence in Thailand. The samples in the research study consisted of ten purposively selected experts in supply chain. he research instruments included supply chain model for universities management according to education Criteria for performance excellence in Thailand and the evaluation form regarding the appropriateness of the model process Data were analysed using mean and standard deviation . The research findings model consists of seven components namely main components ,suppliers, Manufacture, excellence university , Customers, Satisfaction, feedback and to sum up, supply chain model for universities management according to education Criteria for performance excellence in Thailand process is appropriate and applicable to real practice.Â